Skeletal muscle fatigue in long-distance runners, sprinters and untrained men after repeated drop jumps performed at maximal intensity - Skurvydas, A.; Dudoniene, V.; Kalvenas, A.; Zuoza, A. (Scandinavian Journal of Medicine & Science in Sports, 2002)
One hundred drop jumps were performed at maximal intensity every 20 s in 12 untrained subjects (UT), 9 sprinters (S) and 10 long-distance runners (LDR). Muscle contraction force (P20, P50) induced by percutaneous electrical stimulation (20 Hz and 50 Hz, respectively) as well as maximal voluntary contraction force and the height of vertical jumps performed in different ways decreased (P<0.05) and was not restored to the initial value 20 min post exercise. There was a marked increase in low frequency fatigue (LFF) in all the groups studied as substantiated by a significant decrease in the ratio of P20/P50 immediately after exercise as well as 20 min post exercise compared to pre exercise values (P<0.05). However, low frequency fatigue was similar in UT, S and LDR. The jump height of the sprinters during counter-movement jump and drop jump at 90 degrees decreased to a smaller extent compared to jumps performed by LDR and UT. Muscle pain did not differ between UT, S and LDR at 24 h post exercise. The present data indicate that endurance training status as well as prevalence of muscle fibres of the slow type does not decrease muscle resistance to LFF nor accelerate the recovery of muscle contraction force following maximal, intermittent stretch-shortening cycle exercise.